972 EXPLORING THE IMPACT OF FRAILTY FOLLOWING TRAUMA: AN ANALYSIS OF EMERGENCY DEPARTMENT (ED) MANAGEMENT AND LONG TERM OUTCOMES. (14th June 2022) - Cuthbertson, R; Ellis, K; Reda, E; Chaplow, K; Gordon, M W G; Capek, E
Abstract: Introduction: Major trauma represents a large number of hospital presentations in Scotland. 1 We aimed to: -Describe the population of 'major trauma' patients presenting to the Emergency Department of QEUH, Glasgow -Compare assessment, management and clinical outcomes in frail versus non-frail patients with trauma. Method: This was a retrospective, cohort study. Patients were identified using the Scottish Trauma Audit Group (STAG) database. 2 Patients aged over 18, admitted between 01/11/18 and 31/01/19 were included. STAG data was supplemented by individual case note review. Clinical Frailty Scale (CFS) and Charlson Comorbidity Index (CCI) were calculated. Results: 203 patients (173 non-frail, 30 frail) were included. Median age was 58 years (range 19–98). Isolated head injuries were the predominant injury type in frail patients (36.7%) versus polytrauma in non-frail cohort (44.5%). Injury Severity Score (ISS) was similar across both groups (median score: 10v9.5). CCI score correlated well with frailty. Frail patients were less likely to: -Have ambulance pre-alert call (10% v 28%, p = 0.041). -Be managed in 'Resus' (17% v 54%, p < 0.05). -Have consultant-led care in ED (6.6% v 36.4%, p = 0.001). -Undergo CT within 60 minutes (10% v 34.7%, p = 0.0095). They were more likely to be admitted under a Medical Team (20% v 2.9%, p < 0.05). Frailty was associated with poorer outcomes: -Mortality 30% v 9.8%: significant difference in unadjusted, 1-year survival curves (Log-rank test p = 0.0026). Frailty carried a hazard-ratio of death of 5.02 (CI:2.13–11.79, p = 0.0002) compared to non-frailty through the first year after trauma. -Longer median Length of Stay: 22 v 8 days. Conclusion: We identified poorer clinical outcomes in our frail patient cohort. Despite this, and with similar ISS scores across both groups, our data would suggest a tendency to under-recognise significant trauma in Frail patients. References [1] Audit of Trauma Management in Scotland. Public Health Scotland, 2021 [2] Scottish Trauma Audit Group https://www.stag.scot.nhs.uk/